The Relationship between a History of Cesarean Section and The Incidence of Placenta Accreta : A Systematic Review - Bagus Wanda H; Gina Fauziah; Dahlia Winda N (The International Journal of Medical Science and Health Research, 2026)
Background: The global rise in cesarean section (CS) rates has raised concern about subsequent pregnancy complications, particularly placenta accreta spectrum (PAS). This review synthesizes evidence on the relationship between prior CS history and PAS incidence. Methods: A systematic review of 80 studies (RCT, etc) was conducted. Studies required clear PAS diagnostic criteria, comparison groups, and reported association measures between CS history and PAS. Results: Prior CS is consistently associated with increased PAS risk. Klar & Michels reported summary OR 1.96 (95%CI 1.41–2.74) for any prior CS. Keag et al. found OR 2.95 (95%CI 1.32–6.60) for CS vs vaginal delivery. A strong dose-response exists: Silver et al. data show accreta rates of 0.2% (1 CS), 0.3% (2 CS), 0.6% (3 CS), 2.1% (4 CS), 2.3% (5 CS), 6.7% (≥6 CS) in all-comers. With concurrent placenta previa, rates rise dramatically: 3.3% (1 CS), 11.1% (2 CS), 40.0% (3 CS), 61.0% (4 CS), 67.0% (≥5 CS). Iacovelli et al. reported OR 2.6 (1.6–4.4) for 2 prior CS and OR 5.4 (1.7–17.4) for 3 prior CS. Bonanni et al. cited Nordic ORs of 6.6 (4.4–9.8), 17.4 (9.0–31.4), and 55.9 (25.0–110.3) for 1,2,≥3 CS respectively. PAS without previa is less associated with CS (OR 0.15, 95%CI 0.06–0.37, p<0.001) and more with IVF and curettage. Classical CS carries higher accreta risk than low-transverse CS. Isthmocele is an intermediate risk factor. PAS leads to severe morbidity: postpartum hemorrhage 80%, hysterectomy 43.3%, transfusion 23.3%. Discussion: The CS-PAS association is robust, dose-dependent, and mechanistically explained by defective decidualization at the uterine scar. The interaction with placenta previa creates the highest-risk group. Temporal trends show rising PAS incidence alongside CS rates. Conclusion: Prior CS significantly increases PAS risk in a dose-response manner, especially with coexisting placenta previa. Women with multiple prior CS and previa warrant specialized antenatal surveillance and multidisciplinary delivery planning.